Kinetics of Micelle Formation and Concentration Fluctuations in Solutions of Short-Chain Surfactants - Kaatze, U (The journal of physical chemistry. B, 2011)
To study the kinetics of surfactant systems below, at, and above the critical micelle concentration cmc, broad-band ultrasonic spectra of short-chain ionic surfactant solutions are evaluated. Within the measurement frequency range from 100 kHz to 4.6 GHz the spectra reveal a relaxation term that, at variance with the classical theory of micelle formation, is subject to a broad distribution of relaxation times. Analysis of the shape of this term evidences a coupling between the kinetics of micelle formation/disintegration and noncritical fluctuations in the local concentrations of surfactant monomers, oligomers, and micellar structures. A theoretical model, based on the assumption of a rate process in parallel to the fluctuations, applies well to the broadness of the experimental spectra. An initial increase in the concentration dependence of the principle relaxation time above the cmc is compatible with the high content of oligomers but is more distinctive than predicted by an extended model of micelle formation. The dependence of the relaxation amplitude upon surfactant concentration indicates incomplete dissociation of counterions. An additional high-frequency wing in the spectra is assigned to different structure factors of monomers and micelles. It may, however, also contain contributions from relaxations due to the formation/disintegration kinetics of oligomers and to the structural isomerization of surfactant alkyl chains.